Pregnancy after fertility sparing surgery of ovarian cancer stage IC and borderline tumour on contralateral side - Wilczyński, Miłosz; Szpakowski, Marian; Lutosławska, Joanna; Łukaszek, Stanisław; Kucharski, Marek; Wilczyński, Jacek R. (Menopause Review/Przegląd Menopauzalny, 2010)
Serous ovarian cancer prevalence increases with age, and the highest morbidity is reached in women in their seventies. However, this neoplasm is also diagnosed in women in reproductive age. Fertility sparing surgery is performed in women affected by early stage and low-grade ovarian cancer (IA according to FIGO). The patients’ desire to have children forces surgeons to attempt conservative surgery in more advanced stages of ovarian cancer. We present a case of a 19-year-old patient who underwent conservative surgery because of IC epithelial ovarian cancer with borderline tumour on the contralateral ovary. The operation was followed by 6 cycles of adjuvant chemotherapy. 43 months after treatment the patient gave birth and in that time no evidence of recurrence was detected.